Couples: Case - Ginicola, M.M. (Critical Incidents in Integrating Spirituality into Counseling, 2015)
This chapter talks about Michael and Ethan's case study, where two people were involved in being in an interfaith relationship. The author's primary goal was to help each become empathic and to understand the other's position on coming out and being a public couple. A secondary goal was to increase their communication in articulating their feelings surrounding coming out officially. Working from an existential approach, the author encouraged them both to explore their meanings associated with religion, their families, and each other. He used the Emotionally Focused Couples Therapy (EFCT) approach, and insights of integrating sexual orientation and religious identities, spiritual interventions, and dealing with discrimination. Building on the strength-based model, the author identified positive assets that each brought to the relationship individually and in a partnership. Each was willing to develop a plan that represented a middle ground between their two positions. © 2015 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Crit. Incid. in Integr. Spirit. into Couns.
Keywords: Discrimination; Emotionally Focused Couples Therapy; Homosexuality; Religious identities; Same-sex couples; Spiritual Interventions; dept.csp

Military Families: Case - Smith, C. (Critical Incidents in Integrating Spirituality into Counseling, 2015)
This chapter discusses the case of Kelly, a 43-year-old white woman married to an Air Force pilot, came to counseling because she was struggling with several issues. Watching the news about and receiving updates from her husband's command exacerbated Kelly's sense of being overwhelmed and powerless. The author first tried to identify the supports Kelly needed to have in place as she went through her lumpectomy. Second, the counselors explored how to secure resources for James's school issues. According to the author, family counseling sessions should be conducted once Kelly begins to make some minor adjustments and feels more in control. Other possible approaches include solution-focused interventions for short-term results, cognitive-behavioral therapy with Kelly and the children, and family systems theory. As religion is important to Kelly and her husband, the counselor could explore ways to incorporate interventions appropriate to her religious beliefs and values. © 2015 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Crit. Incid. in Integr. Spirit. into Couns.
Keywords: Cognitive-behavioral therapy; Family counseling sessions; Family systems theory; Military families; Religious interventions; Spiritual resources; dept.csp

Financial health and mental health among clients of a community mental health center: making the connections - Harper, Annie; Clayton, Ashley; Bailey, Margaret; Foss-Kelly, Louisa; Sernyak, Michael J.; Rowe, Michael (Psychiatric Services, 2015)
Objectives: This study evaluated financial challenges, satisfaction with financial-management supports, and interest in additional or alternative supports among clients of a mental health center. Methods: Six focus groups were held with 39 clients of an urban community mental health center who reported having difficulty with their finances. Five focus groups were held with direct-care staff who provided services to the clients. Investigators used an inductive analytical approach to distill themes from notes taken during the focus groups. Results: Clients emphasized the challenges of living in poverty and described using complex strategies to sustain themselves, including negotiating benefits systems, carefully planning purchases, and developing and relying on social relationships. They spoke of having uneven access to tools and services for managing their money, such as advice from direct-care staff, representative payees, and bank accounts, and had varying opinions about their value. Noting concerns similar to those of clients, direct-care staff expressed frustration at the lack of support services for helping clients manage their finances. Both clients and staff expressed the need for more services to help clients with their finances. Conclusions: Findings suggest a need for more services to support people with mental illness to manage their finances, particularly a more flexible and broader range of options than are provided by current representative-payee mechanisms.
17 citations (Crossref) [2023-10-31] tex.eissn: 1557-9700 tex.unique-id: ISI:000370847300012
Keywords: Article; Community Mental Health Centers; Connecticut; Focus Groups; Humans; Mental Disorders; Mental Health; Patient Advocacy; Patient Satisfaction; Poverty; Social Support; Urban Population; adult; analytic method; clinical article; clinical assessment; clinical evaluation; community mental health center; coping behavior; dept.csp; economics; female; financial management; health care access; health insurance; human; information processing; interpersonal communication; male; managed care; medical staff; mental disease; mental health; mental health service; money; patient advocacy; patient satisfaction; poverty; social interaction; social support; treatment planning; urban population